Veterans Day events include 5K run Nov. 9 and parade Nov. 11 - Uribes, Tom::::::::: (2013)
The Fresno State Bulldog Marching Band will lead the Fresno Veterans Day Parade in downtown Fresno at 11 a.m. Monday, Nov. 11, while other student groups also observe the occasion over the weekend.